THE EFFECT OF SCHOOL PRINCIPAL SUPERVISION ON TEACHER PERFORMANCE - Isjoni Isjoni (International Journal of Educational Best Practices, 2020)
The teacher is the one who stands at the forefront of the success of the learning process at school. Professional teachers are those who have high performance in their field. High or low of teacher performance can be influenced by several factors, both those that come from within the teacher itself, as well as factors that come from outside themselves. This study aims to analyze the effect of school principal supervision on the performance of teachers in one high school (SMA) in Kampar Regency, Riau Indonesia. The study population was 35 senior high school teachers in Kampar Timur, Kampar Regency. Given the relatively small population, the sample was determined by the total sampling technique. Data was collected by distributing questionnaires for supervision variables, while documentation interviews were used for teacher performance variables. The results of the study show that although there is a positive influence between the supervision of school principals on the performance of teachers in SMAN 1 Kampar Timur Kampar Regency, the total number of influences is (R Square (r2) = 0.410 or accounted for 16.80%. This means that the influence of supervision variables on performance teachers only made of 16.80%, while the remaining 83.20% is determined by other factors.